2012
DOI: 10.4161/epi.7.3.19216
|View full text |Cite
|
Sign up to set email alerts
|

Gene promoter methylation is associated with lung function in the elderly: The normative aging study

Abstract: (2012) Gene promoter methylation is associated with lung function in the elderly: The normative aging study, Epigenetics, 7:3, 261-269,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 56 publications
(29 reference statements)
3
54
1
1
Order By: Relevance
“…Five studies [2123, 25, 26] evaluated the association of lung function with DNA methylation and, of these, two (Qiu et al and Lange et al) also reported associations for COPD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies [2123, 25, 26] evaluated the association of lung function with DNA methylation and, of these, two (Qiu et al and Lange et al) also reported associations for COPD.…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary Clinics at these hospitals and associated hospitals served as additional source of participants [32]Post-bronchodilator FEV1/FVC  < 0.7 and FEV1 < 70% predictedBell et al [22]2012UKTwins UKHealthy unselected volunteers who are a twin (MZ, DZ and singleton) representing the general populationParticipants recruited from media campaigns, initially only middle-aged women were included in the registry but from 1995 onwards, men and women >18 years of age were also recruited [28]Analysed lung function only (no COPD diagnosis) –FEV1 and FVCLepeule et al [25]2012USANormative AgeingHealthy male participants at enrolment, containing smokers and ex-smokers (Veterans Administration 1963 closed-cohort)Enrolled after an initial health screening determined that they were free of known chronic medical conditionsAnalysed lung function –FEV1, FVC, MMEF (did not specify pre-/post-bronchodilator)Lange et al [26]2012Boston (USA)Normative AgeingHealthy male participants at enrolment, containing smokers and ex-smokers (Veterans Administration 1963 closed-cohort)Enrolled after an initial health screening determined that they were free of known chronic medical conditionsGOLD stage II or higher (pre-bronchodilator FEV1/FVC < 0.7 and FEV1 < 80% predicted)Marioni et al [21]2015Scotland (UK)Lothian BirthChildhood inception cohort of ‘healthy b ’ participants with varying lung function, containing smokers, ex-smokers and never smokersIndividuals born in 1936 in the Lothian area were identified using the Community Health Index (registered at a general practitioner) or through media advertisements. The majority of the cohort were participants in the Scottish Mental Survey 1947 [27]Analysed lung function only (no COPD diagnosis)-FEV1Wielscher et al [24]2015AustriaN/ACOPD patients, GOLD 0 COPD patients and healthy controlsSelection of patient from Medical University of Vienna, 2008-2012Post-bronchodilator FEV1/FVC <0.7 Abbreviations : ICGN International COPD Genetics Network a Multi-centre: Cambridge, Copenhagen, Denver, Harvard, Holland, Italy, Liverpool, Nebraska, Spain, Vancouver EOCOPD: Early-onset COPD (Boston), AAT: Alpha-1-Antitrypsin, UK: United Kingdom, MZ: Monozygotic twin, DZ: Dizygotic twin, USA: United States of America, GOLD: Global Initiative for Chronic Obstructive Lung Disease b Healthy: participants free from chronic disease at enrolment, GOLD stage 0: FEV1/FVC ratio > 0.7 but with respiratory symptoms …”
Section: Resultsmentioning
confidence: 99%
“…In the Normative Aging Study, we generated pyrosequencing-based methylation data for nine genes across pathways related to oxidation, blood clotting, and inflammation (Bind et al 2012; Lepeule et al 2012, 2014). We chose to focus our analysis on the four inflammatory genes included in these genes, including two inflammatory cytokines ( IFN- γ and IL-6 ), intercellular adhesion molecule 1 ( ICAM-1 ), and Toll-like receptor 2 ( TLR-2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies in humans have reported associations between blood DNA methylation and cardiovascular diseases (Stenvinkel et al 2007), respiratory health (Lepeule et al 2012), and survival (Baccarelli et al 2010). …”
Section: Introductionmentioning
confidence: 99%